2009
DOI: 10.1080/01639370902737240
|View full text |Cite
|
Sign up to set email alerts
|

Metadata Quality in Digital Repositories: A Survey of the Current State of the Art

Abstract: This study presents the current state of research and practice on metadata quality through focus on the functional perspective on metadata quality, measurement, and evaluation criteria coupled with mechanisms for improving metadata quality. Quality metadata reflect the degree to which the metadata in question perform the core bibliographic functions of discovery, use, provenance, currency, authentication, and administration. The functional perspective is closely tied to the criteria and measurements used for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 6 publications
2
100
0
2
Order By: Relevance
“…They are traditional aspects of librarianship and are included in the Library and Information Sciences curricula, but they have acquired new meaning in the digital era because of the importance of metadata quality in digital repositories. 13 As a matter of fact the accuracy, completeness and consistency of metadata improve the interoperability among repositories and help build an effective digital infrastructure for knowledge dissemination (Park, 2009). …”
Section: Collection Development and Metadatamentioning
confidence: 99%
“…They are traditional aspects of librarianship and are included in the Library and Information Sciences curricula, but they have acquired new meaning in the digital era because of the importance of metadata quality in digital repositories. 13 As a matter of fact the accuracy, completeness and consistency of metadata improve the interoperability among repositories and help build an effective digital infrastructure for knowledge dissemination (Park, 2009). …”
Section: Collection Development and Metadatamentioning
confidence: 99%
“…Metadata are data that describe other data and therefore can be used to control and manage processes. 19 …”
Section: Metadata To Control Extraction and Uploadingmentioning
confidence: 99%
“…Metadata quality is a semantically slippery term. Park [30] suggested that the most commonly accepted criteria for metadata quality are completeness, accuracy, and consistence. Our work is focused on the last criterion.…”
Section: Related Workmentioning
confidence: 99%